Financial Inclusion, Stability, and Governance in the Era of Digital Currencies - Satoto, Eko Budi; Qomariah, Nurul; Yandari, Aprilya Dwi (Indonesian Scientific Publication, 2025)
Digital currencies, including Central Bank Digital Currencies (CBDCs), cryptocurrencies, and stablecoins, are reshaping global financial systems, raising questions about efficiency, inclusion, stability, and regulation. This study aims to provide a narrative review of the opportunities and regulatory impacts of digital currencies within both advanced and emerging economies. Relevant literature was collected from major databases, including Scopus, Web of Science, Google Scholar, IEEE Xplore, and PLOS ONE. Selection emphasized relevance, quality, and contribution to technological, economic, and policy discussions. The results show that CBDCs offer opportunities to enhance financial inclusion and reduce transaction costs, while also strengthening monetary policy effectiveness. Cryptocurrencies and blockchain-based systems have demonstrated efficiency in cross-border transactions but also exhibit volatility and speculative behavior that challenge traditional financial theories. Regulatory frameworks and governance emerge as central issues, with evidence that clear, harmonized, and innovation-friendly regulations accelerate adoption, whereas restrictive policies hinder development. Global comparisons reveal that advanced economies emphasize monetary policy and stability, while developing economies prioritize inclusion. Systemic factors such as infrastructure, literacy, and governance strongly influence adoption outcomes. The findings underscore the urgency of adaptive regulation, international cooperation, and public education as strategies to maximize benefits while mitigating risks. Future research should explore sociopolitical and behavioral aspects, long-term systemic impacts, and regional variations to advance a comprehensive understanding of digital currencies. These insights provide critical guidance for policymakers and financial institutions navigating the digital transformation of money.